Human–Machine Collaboration in Microbiological Laboratories: A Posthuman Perspective on Automation, Control, and Scientific Agency - Patel, Keyur (Journal of Posthumanism, 2024)
The growing adoption of automation and intelligent technology in the microbiological laboratories is transforming the manner in which scientific knowledge is generated, and posing critical challenges of control, autonomy and agency. The current paper identifies the narrative review method to address the topic of human-machine collaboration via Posthumanism. It uses interdisciplinary literature to critically examine the role of automated systems in the way it goes beyond being a passive tool to the active shaping of experimental processes and decision-making. The results propose that scientific agency is not purely human, but it is shared in socio-technical assemblage where machines, algorithms, and biological systems work together to generate knowledge. Nevertheless, this redistribution creates tensions, such as less transparency, an accountability shift, and asymmetrical power relations that are embedded in technological devices. The paper proposes that automation does not only intensify human control but rather remakes it in complicated and mostly non-transparent ways. The post-humanist approach is necessary towards this understanding of the changing nature of scientific practice and in response to the epistemological and ethical aspects of an increasing automated laboratory space.